Assessment of Potential Review in Organizations through HAV MATRIX - Nugrani, Suci; Adiati, Rosatyani Puspita (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The background of this research is the importance of Talent Management in Human Resource Management (HRM). The purpose of Talent Management is to aim at ensuring employees are placed in roles that align with their potential and capabilities (Cummings & Worley, 2015a; Mondy & Martocchio, 2016). Organizations must adopt a systematic approach to identifying employee potential as a basis for strategic decision-making, including promotions, training, and succession planning (Gibson & Mitchell, 2011; Jooss et al., 2021). Potential review serves as a relevant method for objectively assessing individual strengths and weaknesses (Ardhi & Darusmin, 2020; Munandar, 2008). This study aims to support the talent management strategy at PT Z by evaluating employee potential through the Human Asset Value (HAV) Matrix. Amid increasingly complex business dynamics, the strategic management of human resources, particularly in identifying and developing talent, has become increasingly critical. PT Z conducted individual assessments as an initial step to map employee competencies and capacities to support optimal career development planning. A mixed-method approach, comprising psychological testing and interviews, was applied to analyze the data descriptively and qualitatively, resulting in a comprehensive employee profile of an individual serving as an Assistant Analyst for Organizational Culture. The study's findings indicate that the employee possesses strong developmental potential, categorized as